Evidence for a maximum jet efficiency for the most powerful radio galaxies - Fernandes, C; Jarvis, M; Rawlings, S; Martinez-Sansigre, A; Hatziminaoglou, E; Lacy, M; Page, M; Stevens, J; Vardoulaki, E (2010)
We use new mid-infrared (mid-IR) photometry from the Spitzer Space Telescope to study the relations between low-frequency radio luminosity density L_151MHz, mid-IR (12um rest-frame) luminosity L_12um, and optical-emission-line ([OII]) luminosity L_[OII], for a complete sample of z~1 radio galaxies from the 3CRR, 6CE, 6C*, 7CRS and TOOT00 surveys. The narrow redshift span of our sample (0.9